Electrically conductive composites of polyurethane derived from castor oil with polypyrrole‐coated peach palm fibers. Issue 10 (18th September 2015) - Merlini, Claudia; Barra, Guilherme M.O.; da Cunha, Matthäus D.P.P.; Ramôa, Sílvia D.A.S.; Soares, Bluma G.; Pegoretti, Alessandro
Abstract : Electrically conducting fibers were prepared through in situ oxidative polymerization of pyrrole (Py) in the presence of peach palm fibers (PPF) using iron (III) chloride hexahydrate (FeCl3 ·6H2 O) as oxidant. The polypyrrole (PPy) coated PPF displayed a PPy layer on the fibers surface, which was responsible for an electrical conductivity of (2.2 ± 0.3) × 10 −1 S cm −1, similar to the neat PPy. Electrically conductive composites were prepared by dispersing various amounts of PPy‐coated PPF in a polyurethane matrix derived from castor oil. The polyurethane/PPy‐coated PPF composites (PU/PPF–PPy) exhibited an electrical conductivity higher than PU/PPy blends with similar filler content. This behavior is attributed to the higher aspect ratio of PPF–PPy when compared with PPy particles, inducing a denser conductive network formation in the PU matrix. Electromagnetic interference shielding effectiveness (EMI SE) value in the X‐band (8.2–12.4 GHz) found for PU/PPF–PPy composites containing 25 wt% of PPF–PPy were in the range −12 dB, which corresponds to 93.2% of attenuation, indicating that these composites are promising candidates for EMI shielding applications. POLYM. COMPOS., 38:2146–2155, 2017. © 2015 Society of Plastics Engineers